Combined Effects of Wall Squat and Treadmill Walking Exercises on Pain and Functional Disability in Non Specific Chronic Low Back Pain: A Case Report - Prem Jiteshkumar Shah; S Aravind (Journal of Clinical and Diagnostic Research)
Low Back Pain (LBP) is the most prevalent musculoskeletal condition worldwide, significantly affecting daily functioning and quality of life. It is mostly non specific in about 90% of cases, where there is no identifiable disease or structural reason to explain the pain. Physiotherapists play a key role in managing patients with chronic LBP. They use various strategies to alleviate pain, enhance pain tolerance, reduce stress on the lumbar region, strengthen lumbar stabilisers and improve functional abilities. Numerous studies have demonstrated the positive effects of isometric strengthening and aerobic exercise in chronic pain conditions. In this context, the authors present a case of a 22-year-old female patient, demonstrating the positive benefits of a combination of wall squat and treadmill walking exercises to improve pain and functional disability in a patient suffering from non specific chronic LBP.